Global Patterns of Abundance, Diversity and Community Structure of the Aminicenantes (Candidate Phylum OP8) - Farag, Ibrahim F. (Public Library of Science, 2014)
We investigated the global patterns of abundance, diversity, and community structure of members of the Aminicenantes (candidate phylum OP8). Our aim was to identify the putative ecological role(s) played by members of this poorly characterized bacterial lineages in various ecosystems. Analysis of near full-length 16S rRNA genes identified four classes and eight orders within the Aminicenantes. Within 3,134 datasets comprising ∼1.8 billion high throughput-generated partial 16S rRNA genes, 47,351 Aminicenantes-affiliated sequences were identified in 913 datasets. The Aminicenantes exhibited the highest relative abundance in hydrocarbon-impacted environments, followed by marine habitats (especially hydrothermal vents and coral-associated microbiome samples), and aquatic, non-marine habitats (especially in terrestrial springs and groundwater samples). While the overall abundance of the Aminicenantes was higher in low oxygen tension as well as non-saline and low salinity habitats, it was encountered in a wide range of oxygen tension, salinities, and temperatures. Analysis of the community structure of the Aminicenantes showed distinct patterns across various datasets that appear to be, mostly, driven by habitat variations rather than prevalent environmental parameters. We argue that the detection of the Aminicenantes across environmental extremes and the observed distinct community structure patterns reflect a high level of intraphylum metabolic diversity and adaptive capabilities that enable its survival and growth in a wide range of habitats and environmental conditions.